Secondary Education in Ethiopia : Supporting Growth and Transformation - Joshi, Rajendra Dhoj; Verspoor, Adriaan (Washington, DC: World Bank, 2013)
This report is on the secondary education in Ethiopia. The report analyzes the challenges of secondary education in the context of the government's growth and transformation plan and its stated goal of becoming a middle-income country by 2020-23. The education system in Ethiopia as currently organized, together with existing education policies, has served the country well as it has transitioned from a country with some of the lowest enrollment ratios in the world to one where universal primary education is within reach. The current secondary curriculum is not designed to meet the demands of universal general secondary education; it is too difficult and academic for that purpose. The report begins with an investigation of the participation rate in secondary education that would support a middle-income economy. It then examines whether the current secondary curriculum can ensure a supply of secondary graduates compatible with the needs of this economy. The report also analyzes how teacher preparation, development, and management, together with school-based management, can contribute to ensuring quality secondary graduates. Based on the quantity and quality of secondary graduates required, the report then assesses the options for ensuring sustainable financing for the subsector. It concludes with a summary of policy options for the expansion of secondary education. Ethiopia's recent economic performance has been impressive. Sustaining this performance over the coming 15 years will require significant improvements in productivity, which must be achieved through improved management, the application of technology, and the upgrading of human capital. Ensuring that its education system both imparts students with middle-level skills and facilitates improved learning achievement is probably the most critical challenge that Ethiopia faces.